Probing Socio-Pragmatic Skills of L2 Learners of Indonesian on Japanese Politeness - Supriatnaningsih, Rina; Nurjaleka, Lisda; Nurhayati, Silvia; Yani, Damai; Windarti, Yulia (Register Journal, 2024)
This study explores how learners of Japanese as a foreign language in Indonesia comprehend and use Japanese politeness. Many linguists mentioned that socio-pragmatic skills can be developed in a classroom. This skill is essential for L2 learners to master communication in L2, such as how to build and express turn-taking, eye contact and give attention to the interlocutors. Therefore, this study aims to prove whether Indonesian learners of Japanese could use appropriate socio-pragmatic skills, focusing on Japanese politeness in a conversation setting. The subjects are 120 students from two universities whose level of Japanese skills is on the A2-B1 CERF level. We use the role-play method and set a one-on-one conversation/interview setting. Our findings demonstrate that most Indonesian students had difficulty comprehending the concept of ‘Tachiba’, meaning the place where one stands in a Japanese conversation. Most student participants could not yet grasp the social and interaction level. However, in some cases, Japanese politeness in context meaning is found.